2017
DOI: 10.18632/oncotarget.19154
|View full text |Cite
|
Sign up to set email alerts
|

An emerging function of circRNA-miRNAs-mRNA axis in human diseases

Abstract: Circular RNAs (circRNAs), a novel class of long noncoding RNAs, are characterized by a covalently closed continuous loop without 5′ or 3′ polarities structure and have been widely found in thousands of lives including plants, animals and human beings. Utilizing the high-throughput RNA sequencing (RNA-seq) technology, recent findings have indicated thata great deal of circRNAs, which are endogenous, stable, widely expressed in mammalian cells, often exhibit cell type-specific, tissue-specific or developmental-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
347
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(352 citation statements)
references
References 67 publications
4
347
0
1
Order By: Relevance
“…In recent years, circRNA-miRNA-gene regulatory axes were confirmed that involved in pathogenic processes or cancer [46,47]. In order to show a more intuitionistic result, three up-regulated circRNAs (chr5: 51521674-51524828-, chr3: 3137166-3138170+, chr4: 59505289-59510641-) in tumor liver samples of ALV-J-susceptible chickens were selected and five target miRNAs and 10 miRNA target genes were showed in the circRNA-miRNA-gene network which provides a foundation for further pathogenic mechanism research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, circRNA-miRNA-gene regulatory axes were confirmed that involved in pathogenic processes or cancer [46,47]. In order to show a more intuitionistic result, three up-regulated circRNAs (chr5: 51521674-51524828-, chr3: 3137166-3138170+, chr4: 59505289-59510641-) in tumor liver samples of ALV-J-susceptible chickens were selected and five target miRNAs and 10 miRNA target genes were showed in the circRNA-miRNA-gene network which provides a foundation for further pathogenic mechanism research.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that circRNAs play important roles in the regulation of gene expression at the posttranscriptional level [5][6][7]. Accordingly, it has been demonstrated that many circRNAs serve as competing endogenous RNAs to bind with microRNAs (miRNAs) and inhibit the activity and function of the targeted miRNAs [8,9]. With the increasing number of studies on circRNAs, circRNAs have been shown to be involved in the development of several types of diseases, including cancer [10], cardiovascular disease [11], and neurological disorders [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PCK1 and G6PC genes were annotated with the hepatic gluconeogenic related GO term: d-amino-acid oxidase activity (GO: 0003884). Previous study have found PCK1 and G6PC were the predominant genes that encode enzymes involved in the regulation of gluconeogenesis [55]. These results suggest that hepatic gluconeogenesis may be regulated by the influence of lncRNAs on these neighboring protein-coding genes.…”
Section: Discussionmentioning
confidence: 60%